Pengaruh Keputusan Investasi, Pendanaan, dan Kebijakan Dividen terhadap Nilai Perusahaan: Penelitian - Deri Apriadi; Adi Artino; Miftah Faiz Ali Ramdhani; Merry Fithriani; La Ode Marihi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is quantitative, that is, research that aims to determine the causal relationship between two or more variables. This study focuses on analyzing the influence of investment decisions, financing decisions, and dividend policies on company value. The data in this study are secondary data obtained from reports published by the Indonesia Stock Exchange (IDX). The population used in this study were manufacturing companies during the observation years, namely 2020-2024. The data analysis technique in this study used Multiple Linear Regression Analysis with SPSS. The results show that financing decisions and dividend policies have a significant effect on company value. Appropriate financing decisions, especially in determining the optimal capital structure between debt and equity, can reduce the cost of capital and increase the company's financial efficiency, thus positively impacting company value. Meanwhile, a consistent dividend policy that is in line with investor expectations provides a positive signal to the market regarding the company's financial stability and prospects, which ultimately increases investor confidence and the company's stock market value.